Which of the applied methods of identifying green jobs in the economy is the most effective? - Kozar, Łukasz (W poszukiwaniu zielonego ładu, 2022)
Green jobs are those that transfer the theoretical assumptions of the idea of sustainable socio-economic development to economic practice. The chapter reviews the key methods for identifying green jobs in the economy from the point of view of their effectiveness (the possibility of identifying green jobs while underestimating or overestimating them as little as possible). Particular attention was paid to the following methods: sectoral approach, occupations performed and qualitative analysis of workplaces.